Dissociable roles for hippocampal and amygdalar volume in human fear conditioning - Cacciaglia, Raffaele; Flor, Herta (Brain structure & function, 2014)
Fear conditioning is a basic learning process which involves the association of a formerly neutral conditioned stimulus (CS) with a biologically relevant aversive unconditioned stimulus (US). Previous studies conducted in brain-lesioned patients have shown that while the acquisition of autonomic fear responses requires an intact amygdala, a spared hippocampus is necessary for the development of the CS-US contingency awareness. Although these data have been supported by studies using functional neuroimaging techniques in healthy people, attempts to extend these findings to the morphological aspects of amygdala and hippocampus are missing. Here we tested the hypothesis that amygdalar and hippocampal volumes play dissociable roles in determining autonomic responses and contingency awareness during fear conditioning. Fifty-two healthy individuals (mean age 21.83) underwent high-resolution magnetic resonance imaging. We used a differential delay fear conditioning paradigm while assessing skin conductance responses (SCRs), subjective ratings of CS-US contingency, as well as emotional valence and perceived arousal. Left amygdalar volume significantly predicted the magnitude of differential SCRs during fear acquisition, but had no impact on contingency learning. Conversely, bilateral hippocampal volumes were significantly related to contingency ratings, but not to SCRs. Moreover, left amygdalar volume predicted SCRs to the reinforced CS alone, but not those elicited by the US. Our findings bridge the gap between previous lesion and functional imaging studies, by showing that amygdalar and hippocampal volumes differentially modulate the acquisition of conditioned fear. Further, our results reveal that the morphology of these limbic structures moderate learning and memory already in healthy persons.
Gesehen am 26.02.2018